The Arab revolts: Failure or Islamism recomposition? - Moya Mena, Sergio (2012)
The Arab Revolts in the Middle East and North Africa represent major changes for the countries of the region, both politically and socio-cultural. The popular demands that have encouraged these protests are essentially political in character but the role of Islamist movements in countries like Egypt or Tunisia, where they will continue to exert significant influence in the political debates of the post–dictatorship, cannot be ignored.In this paper the author tries to explain the courses of action performed by the Islamists and the possible scenarios of political participation they face in the future.